BOOK REVIEW SOCIOLOGY: UNDERSTANDING A DIVERSE SOCIETY (By: Andersen, Margaret L., and Howard, Francis T., Thomson Learning inc, 2008) - Arif Makmun (Institut Agama Islam Ngawi, 2014)
This book is really good to read which contains comprehensive source of insight into the mechanisms of social interaction between diverse social groups within a certain unit of society. The book is instrumental in providing an overview of the differences in ethnicity, gender, class, religion, as well as the geographical origins of individuals who can greatly influence oneâ€™s system of values, beliefs and stereotypes. The volume is based on extensive research work that has been carried out by the authors and covers a wide range of topics related to such sociological notions as culture, power, social change, stratification, crime, inequality, social interaction and social structure, among others. The first part of the book is focused on a discussion of sociological perspectives. Part two covers the topic of individuals and society and part three is about social inequalities. The fourth part is dedicated to social institutions and mechanisms of their functioning, whereas the fifth and last part covers the notion of social change.Â Â